The The Relationship Of Reading Interest And Learning Style Toward The Students’ Writing Ability At Second Year Students Of SMAN 2 Samarinda - Sulaksono, Agam (Peneliti.net, 2025)
Writing is considered as the most difficult among 4 language skills. To improve it there are some factors that may influence writing abilty. The purposes of this study was to answer whether there is relationship of the students’ reading interest and learning style toward their wrtiting ability. The respondents of this study were 178 students at second year of SMAN 2 Samarinda in the academic year 2024/2025. The data collection technique used in this investigation was a Likert scale with five ordered response options. The Multiple correlation formula was used to analyze the data for determining the relationship of the students’ reading interest and learning style toward their writing ability (Rx₁x₂y). The result of this study showed that There was a significant relationship of reading interest and learning style toward the students’ writing ability proved statistically by the value of Rx₁x₂y which was catagorized as strong correlation, because the value of F test which was greater than the F table. Based on that result, it is important for students to develop their reading interest and their learning style in order that they can enhance their writing ability.